The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1111/j.1440-1789.2011.01279.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase‐9 expression in the nuclear compartment of neurons and glial cells in aging and stroke

Abstract: Matrix metalloproteinases (MMPs) are well-recognized denominators for extracellular matrix remodeling in the pathology of both ischemic and hemorrhagic strokes. Recent data on non-nervous system tissue showed intracellular and even intranuclear localizations for different MMPs, and together with this, a plethora of new functions have been proposed for these intracellular active enzymes, but are mostly related to apoptosis induction and malign transformation. In neurons and glial cells, on human tissue, animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
3
14
1
Order By: Relevance
“… 10 Moreover, in our study at 7 days after tMCAo MMP-9 expression was found in cells with fragmented nuclei ( Figure 4 ) suggesting an associated role in apoptotic processes or to cells undergoing secondary necrosis. 40 , 41 Longitudinal in vivo imaging of MMPs, therefore, may allow the investigation of different pathophysiologic processes after tMCAo with early [ 18 F]BR-351 signals resembling activation of MMPs in the vasculature and subsequent blood–brain barrier opening, intermediate time points (7 to 14 days after tMCAo) indicating activation of microglia and apoptosis, and later time points (14 to 21 days after tMCAo) marking MMP-related neoangiogenesis. 10 It has been shown that early inhibition of MMP-9 has a beneficial role, 39 whereas late inhibition has detrimental effects 10 on stroke outcome.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Moreover, in our study at 7 days after tMCAo MMP-9 expression was found in cells with fragmented nuclei ( Figure 4 ) suggesting an associated role in apoptotic processes or to cells undergoing secondary necrosis. 40 , 41 Longitudinal in vivo imaging of MMPs, therefore, may allow the investigation of different pathophysiologic processes after tMCAo with early [ 18 F]BR-351 signals resembling activation of MMPs in the vasculature and subsequent blood–brain barrier opening, intermediate time points (7 to 14 days after tMCAo) indicating activation of microglia and apoptosis, and later time points (14 to 21 days after tMCAo) marking MMP-related neoangiogenesis. 10 It has been shown that early inhibition of MMP-9 has a beneficial role, 39 whereas late inhibition has detrimental effects 10 on stroke outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Within the resting brain, it is mostly synthesized by neurons but to some extent also by glia in such structures as the hippocampus, cerebral cortex, and cerebellum. It is extracellularly secreted, although recent studies have also revealed its presence in the nucleus of muscle cells (Yeghiazaryan et al, 2012), neurons (Yang et al, 2010; Hill et al, 2012), human glial cells (Pirici et al, 2012), and mitochondria of retinal capillary cells. MMP-9 may act as a negative regulator of mitochondrial function and may be involved in apoptosis (Kowluru et al, 2011).…”
Section: Matrix Metalloproteinase-9mentioning
confidence: 99%
“…Moreover, MMP-13 was found in the nuclei of neurons after cerebral ischaemia in rat brains (Cuadrado et al, 2009), and ADAMTS13 was present within the nuclei of liver-derived cell lines (Hunt et al, 2011). Nuclear localisation of MMP-9 was detected in human and rat neurons, as well as human glial cells (Yang et al, 2010;Pirici et al, 2011), neuroblastoma cells and bone marrow macrophages (Sans-Fons et al, 2010). Although these MMPs were found within the nuclei their function remain elusive, and so far has only been characterised for MMP-2, which degrades poly(ADP-ribose) polymerase (Kwan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%